PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI RIAU - Rexa Ananda; Ani Widayatsari; Harlen Harlen (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
The aim is to analyze the effect of economic growth and minimum wages on employment in Riau Province. Labor absorption in this study refers to the process by which the workforce population is absorbed or trained in various economic sectors. In this study, data processing was performed using multiple linear regression analysis with the Simple Least Squares method (Ordinary Least Square/OLS). The results showed that there was a significant and positive effect between economic growth on employment and there was a significant and positive effect between the minimum wage on labor absorption. Keywords: Economic growth, minimum wage, employment